Highly conductive lithium cobalt oxide precursor and preparation method thereof

By adopting a high-conductive lithium cobalt oxide precursor with a double-layer coated structure, the problems of poor structural stability and insufficient conductivity of lithium cobalt oxide positive electrode materials under high voltage are solved, and significant stability and conductivity are improved.

CN116553624BActive Publication Date: 2025-03-28CNMC NINGXIA ORIENT GRP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310475196.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-27
Publication Date
2025-03-28
Estimated Expiration
2043-04-27

AI Technical Summary

Technical Problem

The existing lithium cobalt oxide cathode materials have poor structural stability and insufficient conductivity at high voltages.

Method used

A highly conductive lithium cobalt oxide precursor adopting a double-layer cladding structure includes a body, an inner cladding layer and an outer cladding layer. The body is cobalt tetroxide, the inner coating is lithium cobalt phosphate, and the outer coating is a doped layer of molybdenum oxide, indium oxide and cobalt tetroxide.

Benefits of technology

The stability and conductivity of lithium cobalt oxide cathode material under high pressure are significantly improved, and the cycle performance and rate performance are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116553624B_ABST
    Figure CN116553624B_ABST
Patent Text Reader

Abstract

A highly conductive lithium cobalt oxide precursor includes a body, an inner coating layer, and an outer coating layer, wherein the body includes cobalt trioxide, the inner coating layer includes lithium cobalt phosphate, and the outer coating layer includes molybdenum oxide, indium oxide, and cobalt trioxide. The lithium cobalt oxide precursor of the present invention has two coating layers, wherein the inner coating layer is lithium cobalt phosphate with an olivine structure, which can inhibit the crystal transformation of lithium cobalt oxide under high pressure, thereby improving the stability of lithium cobalt oxide under high pressure; the outer coating layer is a doped coating layer, and the sintered lithium cobalt oxide positive electrode material contains molybdenum oxide, indium oxide, and lithium cobalt oxide, and molybdenum oxide and indium oxide can provide a conductive channel for lithium cobalt oxide, thereby significantly improving the conductivity of the lithium cobalt oxide positive electrode material. At the same time, an interactive interface will be formed between the body and the inner coating layer, and between the inner layer and the outer coating layer, that is, an inward extension layer and an outward extension layer, which are less likely to peel off.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery positive electrode materials, and in particular relates to a high-conductivity lithium cobalt oxide precursor and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are widely used in new energy vehicles, consumer electronics, power tools and other industries due to their high energy density, long cycle life, high potential and no memory effect. As one of the earliest commercial cathode materials, lithium cobalt oxide has a theoretical capacity of up to 274mAh / g, but the actual specific capacity is often limited to 170mAh / g (cut-off voltage is 4.4V), which is equivalent to 38% of lithium ions not participating in redox. Increasing the cut-off voltage to increase the capacity of lithium cobalt oxide is currently the most effective method. Increasing the cut-off voltage means that more lithium ions are deintercalated from lithium cobalt oxide, which causes the crystal structure of lithium cobalt oxide to expand and transform from the original hexagonal system to the monoclinic system, which causes the structure of lithium cobalt oxide to be destroyed, significantly reducing its capacity and cycle performance. The most common solutions are two-fold: first, metal ion doping; second, surface coating. The doping elements are generally Al, Mg, Ti, Ge, Sn, etc.; by inhibiting the phase change of the material, the stability of the material under high voltage is improved. Surface coating is to coat the surface of the positive electrode material with a thin layer of material to prevent the lithium cobalt oxide positive electrode material from directly contacting the electrolyte. However, none of the above methods have achieved a good practical level, and the electrochemical performance needs to be further improved.

[0003] So far, in order to improve the electrochemical performance of lithium cobalt oxide cathode materials, the main direction of researchers is doping and coating, such as using bulk doping of graphene or other carbon materials in basic cobalt carbonate and bulk tin doping of cobalt carbonate. The results show that the conductivity of the material has improved, but it is still in the laboratory stage and does not meet the conditions for industrial application. At the same time, bulk doping cannot meet the conductivity between particles and cannot play a substantial role. Summary of the invention

[0004] In view of this, it is necessary to provide a highly conductive lithium cobalt oxide precursor for use in industry, which can solve both the problem of poor structural stability of lithium cobalt oxide positive electrode materials under high voltage and the problem of non-conductivity of lithium cobalt oxide positive electrode materials.

[0005] The invention also provides a method for preparing a highly conductive lithium cobalt oxide precursor.

[0006] A high-conductivity lithium cobalt oxide precursor comprises a body, an inner coating layer and an outer coating layer. The body comprises cobalt tetroxide, the inner coating layer comprises lithium cobalt phosphate, and the outer coating layer comprises molybdenum oxide, indium oxide and cobalt tetroxide.

[0007] In the above-mentioned high-conductivity lithium cobalt oxide precursor, preferably, the mass percentage of molybdenum oxide, indium oxide and cobalt tetraoxide is 1:1:(2×10 4 ~4×10 4 ).

[0008] In the above-mentioned high-conductivity lithium cobalt oxide precursor, preferably, the main body also includes aluminum element, and the content of aluminum element in the main body is 4000-6000 ppm.

[0009] In the above-mentioned high-conductivity lithium cobalt oxide precursor, preferably, the content of lithium element in the high-conductivity lithium cobalt oxide precursor is 1500-2500 ppm.

[0010] In the above-mentioned high-conductivity lithium cobalt oxide precursor, preferably, the content of indium element in the high-conductivity lithium cobalt oxide precursor is 1500-3000 ppm, and the content of molybdenum element is 1500-3000 ppm.

[0011] A method for preparing a highly conductive lithium cobalt oxide precursor comprises the following steps:

[0012] Step S1, preparing raw materials:

[0013] Preparing a soluble lithium phosphate salt solution of a predetermined concentration for standby use;

[0014] Preparing a soluble indium salt solution of a predetermined concentration for standby use;

[0015] Prepare a soluble molybdenum salt solution of a predetermined concentration for standby use;

[0016] Prepare a complexing agent solution of a predetermined concentration for standby use;

[0017] Prepare a precipitant solution of a predetermined concentration for standby use;

[0018] Preparing a cobalt salt solution of a predetermined concentration for standby use;

[0019] Prepare aluminum-doped cobalt carbonate for standby use;

[0020] Step S2, adding a predetermined amount of pure water and a predetermined amount of prepared aluminum-doped cobalt carbonate into a reactor, starting stirring and controlling the speed to 60-200 r / min, and maintaining the temperature of the liquid in the reactor at 40-55° C. to generate a bulk intermediate, wherein the effective component is aluminum-doped cobalt carbonate;

[0021] Step S3, adding the prepared complexing agent solution, cobalt salt solution and lithium phosphate salt solution into the reactor at a predetermined flow rate, the pH of the reaction process is 6.5-7.8, until the precipitation in the reactor is complete, the coating is completed, and the inner coating layer intermediate is generated; then washing with pure water and drying; Step S4, putting the dried coating material containing the inner coating layer intermediate back into the reactor, adding a predetermined amount of pure water, starting stirring and controlling the speed at 60-200r / min, and maintaining the liquid temperature in the reactor at 40-55°C;

[0022] Step S5, adding the prepared complexing agent solution, cobalt salt solution, lithium phosphate salt solution and precipitant solution to the reactor at a predetermined flow rate, the pH of the reaction process is 6.5-7.8, after the particle size of the coating material increases by 0.5 microns, adding the prepared molybdenum salt solution and indium salt solution to the reactor at a predetermined flow rate, and stopping the addition of lithium phosphate salt solution to form a composite cobalt carbonate precipitate containing an outer coating layer intermediate, and then continuing to stir for a predetermined time;

[0023] Step S6, washing and drying the composite cobalt carbonate, and then sintering it in a sintering furnace to form a highly conductive lithium cobalt oxide precursor, wherein the main body is cobalt tetroxide, the inner coating layer is a lithium cobalt phosphate layer, and the outer coating layer is a highly conductive indium oxide, molybdenum oxide and cobalt tetroxide doping layer.

[0024] In the method for preparing the above-mentioned high-conductivity lithium cobalt oxide precursor, in step S1, the concentration of the soluble lithium phosphate salt solution is 0.1-1.0 mol / L; the concentration of the soluble indium salt solution is 0.1-2 mol / L; the concentration of the soluble molybdenum salt solution is 0.1-2 mol / L; the concentration of the complexing agent is 1-6 mol / L; the concentration of the precipitant solution is 1-6 mol / L; and the concentration of the cobalt salt solution is 1-3 mol / L.

[0025] In the above-mentioned method for preparing the highly conductive lithium cobalt oxide precursor, the soluble lithium phosphate salt includes but is not limited to one of lithium phosphate, lithium dihydrogen phosphate, and lithium metaphosphate.

[0026] In the above-mentioned method for preparing the highly conductive lithium cobalt oxide precursor, the soluble indium salt includes but is not limited to one of indium trichloride, indium sulfate, indium nitrate and indium perchlorate.

[0027] In the above-mentioned method for preparing the highly conductive lithium cobalt oxide precursor, the soluble molybdenum salt includes but is not limited to one of sodium molybdate and ammonium molybdate.

[0028] In the above-mentioned method for preparing the highly conductive lithium cobalt oxide precursor, the complexing agent includes but is not limited to ammonia water.

[0029] In the above method for preparing the highly conductive lithium cobalt oxide precursor, the precipitant includes but is not limited to one of sodium carbonate, sodium bicarbonate, and ammonium bicarbonate.

[0030] In the above-mentioned method for preparing the highly conductive lithium cobalt oxide precursor, the cobalt salt includes but is not limited to one of cobalt sulfate and cobalt chloride.

[0031] In the above method for preparing the highly conductive lithium cobalt oxide precursor, in step S2 and step S4, the volume of the reaction kettle is 100 L, and the amount of pure water added is 50 L.

[0032] In the above method for preparing the highly conductive lithium cobalt oxide precursor, in step S3, the flow rate of the complexing agent solution is 10-150 ml / min, the flow rate of the cobalt salt solution is 10-150 ml / min, and the flow rate of the lithium phosphate salt solution is 10-50 ml / min.

[0033] In the above-mentioned method for preparing the high-conductivity lithium cobalt oxide precursor, in step S5, the flow rate of the complexing agent solution is 10-150 ml / min, the flow rate of the cobalt salt solution is 10-150 ml / min, the flow rate of the precipitant solution is 10-150 ml / min, the flow rate of the molybdenum salt solution is 10-50 ml / min, and the flow rate of the indium salt solution is 10-50 ml / min.

[0034] Beneficial effects: The lithium cobalt oxide precursor of the present invention has two coating layers, wherein the inner coating layer is lithium cobalt phosphate with an olivine structure, which can inhibit the crystal transformation of lithium cobalt oxide under high pressure, thereby improving the stability of lithium cobalt oxide under high pressure; the outer coating layer is a doped coating layer, and the sintered lithium cobalt oxide positive electrode material contains molybdenum oxide and indium oxide as well as lithium cobalt oxide. Molybdenum oxide and indium oxide can provide a conductive channel for lithium cobalt oxide, thereby significantly improving the conductivity of the lithium cobalt oxide positive electrode material. At the same time, an interactive interface will be formed between the main body and the inner coating layer, and between the inner layer and the outer coating layer, that is, an inward extension layer and an outward extension layer, which are less likely to peel off. The lithium cobalt oxide precursor containing a double coating layer can maintain good stability under high voltage electricity, inhibit crystal transformation, and has high cycle performance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a schematic diagram of the internal structure principle of the high-conductivity lithium cobalt oxide precursor of the present invention.

[0036] Figure 2 It is a schematic diagram of the process flow of the present invention.

[0037] In the figure: a main body 10 , an inner covering layer 20 , an inwardly extending layer 21 , an outwardly extending layer 22 , and an outer covering layer 30 . DETAILED DESCRIPTION

[0038] The scheme of the present invention is described in detail below.

[0039] Please see Figure 1 A high-conductivity lithium cobalt oxide precursor includes a main body, an inner coating layer, and an outer coating layer. The main body includes cobalt tetroxide, the inner coating layer includes lithium cobalt phosphate, and the outer coating layer includes molybdenum oxide, indium oxide and cobalt tetroxide.

[0040] The main body refers to a precursor without an inner coating layer and an outer coating layer. The main body can be formed by sintering cobalt hydroxide or cobalt carbonate.

[0041] In a preferred embodiment, the mass percentage of molybdenum oxide, indium oxide and cobalt oxide is 1:1:(2×10 4 ~4×10 4 )

[0042] In a preferred embodiment, the composition of the body also includes aluminum, and the content of aluminum in the body is 4000-6000 ppm.

[0043] In a preferred embodiment, the content of lithium element in the high-conductivity lithium cobalt oxide precursor is 1500-2500 ppm.

[0044] In a preferred embodiment, the content of indium in the high-conductivity lithium cobalt oxide precursor is 1500-3000 ppm, and the content of molybdenum is 1500-3000 ppm.

[0045] Please see Figure 2 :A method for preparing a highly conductive lithium cobalt oxide precursor comprises the following steps:

[0046] Step S1, preparing raw materials:

[0047] Preparing a soluble lithium phosphate salt solution of a predetermined concentration for standby use;

[0048] Preparing a soluble indium salt solution of a predetermined concentration for standby use;

[0049] Prepare a soluble molybdenum salt solution of a predetermined concentration for standby use;

[0050] Prepare a complexing agent solution of a predetermined concentration for standby use;

[0051] Prepare a precipitant solution of a predetermined concentration for standby use;

[0052] Preparing a cobalt salt solution of a predetermined concentration for standby use;

[0053] Prepare aluminum-doped cobalt carbonate for standby use;

[0054] Step S2, adding a predetermined amount of pure water and a predetermined amount of prepared aluminum-doped cobalt carbonate into a reactor, starting stirring and controlling the speed to 60-200 r / min, and maintaining the temperature of the liquid in the reactor at 40-55° C. to generate a bulk intermediate, wherein the effective component is aluminum-doped cobalt carbonate;

[0055] In a preferred embodiment, the amount of aluminum-doped cobalt carbonate added is 5-10 Kg.

[0056] Step S3, add the configured complexing agent solution, cobalt salt solution and lithium phosphate salt solution to the reactor at a predetermined flow rate, the pH of the reaction process is 6.5-7.8, until the precipitation in the reactor is complete, the coating is completed, and the inner coating layer intermediate is generated; then washed with pure water and dried; in this step, the complexing agent solution, cobalt salt solution, and lithium phosphate salt react to generate lithium cobalt phosphate, that is, the inner coating layer intermediate is generated. At the same time, the lithium phosphate salt will also react with the cobalt carbonate on the surface of the body to generate lithium cobalt phosphate. In this way, an inward extension layer is formed between the body and the inner coating layer intermediate, and the body and the inner coating layer are not clearly distinguished. If it is clearly distinguished, then due to the different compositions between the body and the inner coating layer, their thermal expansion and contraction coefficients are different, which will lead to the shedding of the coating layer caused by factors such as thermal expansion and contraction.

[0057] Step S4, putting the dried coating material containing the inner coating layer intermediate back into the reactor, adding a predetermined amount of pure water, starting stirring and controlling the speed at 60-200 r / min, and maintaining the liquid temperature in the reactor at 40-55° C.;

[0058] Step S5, adding the prepared complexing agent solution, cobalt salt solution, lithium phosphate salt solution and precipitant solution to the reactor at a predetermined flow rate, the pH of the reaction process is 6.5-7.8, after the particle size of the coating material increases by 0.5 microns, adding the prepared molybdenum salt solution and indium salt solution to the reactor at a predetermined flow rate, and stopping the addition of lithium phosphate salt solution to form a composite cobalt carbonate precipitate containing an outer coating layer intermediate, and then continuing to stir for a predetermined time;

[0059] The addition of the complexing agent solution, the cobalt salt solution, the lithium phosphate salt solution and the precipitant solution at the beginning of step S5 is to form an outward extension layer intermediate between the inner coating layer intermediate and the outer coating layer, that is, a mixture of lithium cobalt phosphate and lithium carbonate. Therefore, it should be understood that the amount of lithium phosphate salt used should be less than the amount of its reaction with lithium carbonate. Otherwise, the outward extension layer intermediate will be completely lithium cobalt phosphate without lithium carbonate. Afterwards, after stopping the addition of lithium phosphate salt, the complexing agent, cobalt salt, precipitant, molybdenum salt and indium salt in the solution react to form an outer coating layer intermediate of molybdate, indium hydroxide and cobalt carbonate. The outward extension layer contains the lithium cobalt phosphate contained in the inner coating layer intermediate, and also contains the cobalt carbonate contained in the outer coating layer intermediate. In the precursor formed after subsequent sintering, the generated outward extension layer interacts with the inner coating layer and the outer coating layer. In a preferred embodiment, the continuous stirring time is 1 hour. During the process of adding the molybdenum salt solution and the indium salt solution, the complexing agent solution, the cobalt salt solution and the precipitant solution are continuously added, so that the formed outer coating layer has molybdate, indium hydroxide and cobalt carbonate.

[0060] Step S6, washing and drying the composite cobalt carbonate, and then sintering it in a sintering furnace to form a highly conductive lithium cobalt oxide precursor, wherein the main body is cobalt tetroxide, the inner coating layer is a lithium cobalt phosphate layer, and the coating layer is a doping layer of highly conductive indium oxide, molybdenum oxide and cobalt tetroxide.

[0061] In this step, before sintering, the performance of the dried carbon valley powder is tested, and the test results are shown in Table 1 below.

[0062] Product batch number: SHCOCO3-4A-230401

[0063] Product weight: kg Product name: Cobalt carbonate

[0064] Inspection items unit Test results Co % 47.94 Fe % 0.0013 Mg % <0.0005 Ca % 0.0005 Cu % <0.0005 Zn % <0.0005 Cr % 0.0005 A1 % 0.2317 Si % <0.0005 Na % 0.0055 Pb % 0.0014 K % <0.0005 Magnetic material content <![CDATA[ ppb ]]> 84 <![CDATA[Cl - ]]> % 0.0011 S % 0.0417 <![CDATA[H2O]]> % 0.40 <![CDATA[D3]]> <![CDATA[ μm ]]> 0.162 <![CDATA[D 10 ]]> <![CDATA[ μm ]]> 4.225 <![CDATA[D 30 ]]> <![CDATA[ μm ]]> 5.933 <![CDATA[D 30 ]]> <![CDATA[ μm ]]> 8.113 <![CDATA[D 200 ]]> <![CDATA[ μm ]]> 11.546 Tap density <![CDATA[g / cm 3 ]]> 1.66 / 1.70 Specific surface area <![CDATA[m 2 / g]]> 6.52

[0065] Analysis of the table shows that the cobalt content reaches 47.94%, which exceeds the standard level, indicating that the loss of cobalt elements is within the control range during the use of this method, and the effective conversion rate of cobalt elements reaches 47.94%. The table shows the particle size distribution. The particle size of the product to be produced and controlled by this method is 6±1um, that is, the D60 requirement is greater than 60%. The above table analysis shows that D0, D10, D50, D90, and D100 account for a total of 29.979, and the remaining process requirement particle size distribution accounts for 70.021%. It can be seen that in order to obtain double-layer coating, this method has been coated with an inner coating layer and an outer coating layer, and the number of processes has increased, and the operating process flow has been lengthened, but the proportion of product particle size that meets the process requirement size after coating is still greater than 70%. It can be seen that the process control is fine and controllable, the particle size is good, and the particle size will not be destroyed because of the pursuit of the intact stability and cyclicity of the double-layer coating. The above table also shows that the tap density reaches 1.70 and the specific surface area is 6.52. The larger the tap density, the more powder content per unit volume and the larger the potential specific volume. At the same time, the larger the specific surface area, the larger the specific volume of the powder per unit volume and the larger the capacitance. However, if the tap density is too large, the powder particles will be too crowded, resulting in a large loss of specific surface area. After the positive electrode material is formed, the charging and discharging channels will be blocked and the capacity will be significantly reduced, which will directly lead to an increase in the resistivity of the positive electrode material and a decrease in the cyclability. Therefore, the powder formed by this method has a relatively high and reasonable tap density and specific surface area, which ensures a large capacity without affecting the resistivity and cyclability.

[0066] Specifically, during the sintering process, the aluminum-doped cobalt carbonate of the bulk intermediate generates aluminum-doped cobalt tetroxide at high temperature; the outer coating layer intermediate reacts to generate molybdenum oxide, indium oxide, and cobalt tetroxide.

[0067] In step S6, in a preferred embodiment, the sintering process of the lithium cobalt oxide precursor is: heating from 0-400°C for 5 hours, keeping the temperature for 3 hours, then heating from 450-800°C for 6 hours, keeping the temperature for 5 hours, and finally cooling naturally.

[0068] The inner coating layer is composed of lithium cobalt phosphate, which is not conductive itself, but the olivine structure is more stable under high voltage conditions, which can provide good protection for the main body of lithium cobalt oxide and inhibit the structural deformation of the main body, thereby better maintaining the battery capacity and improving the battery's cycle performance. The indium oxide and molybdenum oxide of the outer coating layer can provide a conductive channel for lithium cobalt oxide, making the lithium cobalt oxide positive electrode material highly conductive. At the same time, the inward extension layer and the outward extension layer can play a "bonding role" for the double-layer coating precursor to prevent the coating layer from stratifying and falling off.

[0069] The prepared conductive lithium cobalt oxide precursor can be evenly mixed with lithium hydroxide in a molar ratio of cobalt element to lithium element of 1:1.3, and then sintered in an air atmosphere at a sintering temperature of 1100°C, sintering for 24 hours, and a heating rate of 4°C / min. After sintering, it is cooled, crushed, and sieved to obtain a lithium cobalt oxide positive electrode material.

[0070] In a preferred embodiment, in step S1, the concentration of the soluble lithium phosphate salt solution is 0.1-1.0 mol / L; the concentration of the soluble indium salt solution is 0.1-2 mol / L; the concentration of the soluble molybdenum salt solution is 0.1-2 mol / L; the concentration of the complexing agent is 1-6 mol / L; the concentration of the precipitant solution is 1-6 mol / L; and the concentration of the cobalt salt solution is 1-3 mol / L.

[0071] In a preferred embodiment, the soluble lithium phosphate salt includes but is not limited to one of lithium phosphate, lithium dihydrogen phosphate, and lithium metaphosphate.

[0072] In a preferred embodiment, the soluble indium salt includes but is not limited to one of indium trichloride, indium sulfate, indium nitrate, and indium perchlorate.

[0073] In a preferred embodiment, the soluble molybdenum salt includes but is not limited to one of sodium molybdate and ammonium molybdate.

[0074] In a preferred embodiment, the complexing agent includes but is not limited to ammonia water.

[0075] In a preferred embodiment, the precipitant includes but is not limited to one of sodium carbonate, sodium bicarbonate, and ammonium bicarbonate.

[0076] In a preferred embodiment, the cobalt salt includes but is not limited to one of cobalt sulfate and cobalt chloride.

[0077] In a preferred embodiment, in step S2 and step S4, the volume of the reactor is 100 L, and the amount of pure water added is 50 L.

[0078] In a preferred embodiment, in step S3, the flow rate of the complexing agent solution is 10-150 ml / min, the flow rate of the cobalt salt solution is 10-150 ml / min, and the flow rate of the lithium phosphate salt solution is 10-50 ml / min.

[0079] In a preferred embodiment, in step S5, the flow rate of the complexing agent solution is 10-150 ml / min, the flow rate of the cobalt salt solution is 10-150 ml / min, the flow rate of the lithium phosphate salt solution is 10-50 ml / min, the flow rate of the precipitant solution is 10-150 ml / min, the flow rate of the molybdenum salt solution is 10-50 ml / min, and the flow rate of the indium salt solution is 10-50 ml / min.

[0080] The effects of the present invention will be described below in conjunction with specific embodiments.

[0081] In order to verify the stability effect and high conductivity of the positive electrode material prepared by the high-conductivity lithium cobalt oxide precursor of the present invention, the electrical performance tests of metal ion doping, graphene doping and surface coating were carried out on the lithium cobalt oxide positive electrode material. The doped and coated materials are conventional doped and coated materials in the art, and the final electrical performance tests are shown in Table 2 below, where the cyclicity test is carried out under high-voltage environment:

[0082] Table 2: Electrical performance test of doped and coated positive electrode materials:

[0083] Resistivity Cyclic performance (0.5C-600 cycles) Doped Alumina Non-conductive 72.3% Doped MgO Non-conductive 64% Doped Titanium Oxide Non-conductive 76% Doped Germanium Oxide Non-conductive 79% Doped graphene / 92% Doped Molybdenum Oxide <![CDATA[10 -5 Ohm cm]]> 91.5% Doped Indium Oxide <![CDATA[10 -4 Ohm cm]]> 86% Doped Tin Oxide <![CDATA[10 -2 Ohm cm]]> 89% Doped Indium Tin Oxide <![CDATA[10 -4 Ohm cm]]> 93% Coated Alumina Non-conductive 79.5% Coated titanium oxide Non-conductive 78.3% The present invention <![CDATA[10 -7 -10 -8 Ohm cm]]> 95%

[0084] Among them, the resistivity can reflect the conductivity of the positive electrode material, and the cyclability can reflect the stability of the positive electrode material under high voltage environment. In this test result, the resistivity can be as low as 10 -7 -10 -8 Ω·cm, and the cyclability can reach 95%, far exceeding the technical effects of other solutions. The excellent resistivity and cyclability of this solution are mainly formed by the double-layer coating structure and process, and the present invention detects the performance of the cobalt carbonate powder before sintering as a reference for process performance, which can characterize the excellent performance of the cobalt carbonate powder before sintering, thereby ensuring the superiority of the performance after sintering and after preparing the positive electrode material. Therefore, it can be seen that the high-conductivity lithium cobalt oxide precursor of the present invention has significant high conductivity and high stability effects.

[0085] What is disclosed above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. A person skilled in the art can understand that all or part of the processes of the above embodiments and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A highly conductive lithium cobalt oxide precursor, characterized in that: The invention comprises a main body, an inner coating layer and an outer coating layer. The main body comprises cobalt tetroxide, the inner coating layer comprises lithium cobalt phosphate, and the outer coating layer comprises molybdenum oxide, indium oxide and cobalt tetroxide.

2. The highly conductive lithium cobalt oxide precursor according to claim 1, characterized in that: The mass percentage of molybdenum oxide, indium oxide and cobalt tetroxide is 1:1:(2×10 4 ~4×10 4 ).

3. The highly conductive lithium cobalt oxide precursor according to claim 1, characterized in that: The main body also includes aluminum, and the aluminum content in the main body is 4000-6000ppm.

4. The highly conductive lithium cobalt oxide precursor according to claim 1, wherein: The content of lithium element in the highly conductive lithium cobalt oxide precursor is 1500-2500 ppm.

5. The highly conductive lithium cobalt oxide precursor according to claim 1, characterized in that: The content of indium in the highly conductive lithium cobalt oxide precursor is 1500-3000 ppm, and the content of molybdenum is 1500-3000 ppm.

6. A method for preparing a highly conductive lithium cobalt oxide precursor according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1, preparing raw materials: preparing a soluble lithium phosphate salt solution of a predetermined concentration for standby use; A soluble indium salt solution of a predetermined concentration is prepared for standby use; a soluble molybdenum salt solution of a predetermined concentration is prepared for standby use; a complexing agent solution of a predetermined concentration is prepared for standby use; a precipitant solution of a predetermined concentration is prepared for standby use; a cobalt salt solution of a predetermined concentration is prepared for standby use; and aluminum-doped cobalt carbonate is prepared for standby use; Step S2, adding a predetermined amount of pure water and a predetermined amount of prepared aluminum-doped cobalt carbonate into a reactor, starting stirring and controlling the speed to 60-200 r / min, and maintaining the temperature of the liquid in the reactor at 40-55° C. to generate a bulk intermediate, wherein the effective component is aluminum-doped cobalt carbonate; Step S3, adding the prepared complexing agent solution, cobalt salt solution and lithium phosphate salt solution into the reactor at a predetermined flow rate, with the pH value of the reaction process being 6.5-7.8, until the precipitation in the reactor is complete and the coating is completed, thereby generating an inner coating layer intermediate; Then wash with pure water and dry; Step S4, putting the dried coating material containing the inner coating layer intermediate back into the reactor, adding a predetermined amount of pure water, starting stirring and controlling the speed at 60-200 r / min, and maintaining the liquid temperature in the reactor at 40-55° C.; Step S5, adding the prepared complexing agent solution, cobalt salt solution, lithium phosphate salt solution and precipitant solution to the reactor at a predetermined flow rate, the pH of the reaction process is 6.5-7.8, after the particle size of the coating material increases by 0.5 microns, adding the prepared molybdenum salt solution and indium salt solution to the reactor at a predetermined flow rate, and stopping the addition of lithium phosphate salt solution to form a composite cobalt carbonate precipitate containing an outer coating layer intermediate, and then continuing stirring for a predetermined time; Step S6, washing and drying the composite cobalt carbonate, and then sintering it in a sintering furnace to form a highly conductive lithium cobalt oxide precursor, wherein the main body is cobalt tetroxide, the inner coating layer is a lithium cobalt phosphate layer, and the outer coating layer is a highly conductive indium oxide, molybdenum oxide and cobalt tetroxide doping layer.

7. The method for preparing a highly conductive lithium cobalt oxide precursor according to claim 6, wherein: In step S1, the concentration of the soluble lithium phosphate salt solution is 0.1-1.0 mol / L; the concentration of the soluble indium salt solution is 0.1-2 mol / L; the concentration of the soluble molybdenum salt solution is 0.1-2 mol / L; the concentration of the complexing agent is 1-6 mol / L; the concentration of the precipitant solution is 1-6 mol / L; and the concentration of the cobalt salt solution is 1-3 mol / L.

8. The method for preparing a highly conductive lithium cobalt oxide precursor according to claim 6, wherein: In step S2 and step S4, the volume of the reactor is 100 L, and the amount of pure water added is 50 L.

9. The method for preparing a highly conductive lithium cobalt oxide precursor according to claim 6, wherein: In step S3, the flow rate of the complexing agent solution is 10-150 ml / min, the flow rate of the cobalt salt solution is 10-150 ml / min, and the flow rate of the lithium phosphate salt solution is 10-50 ml / min.

10. The method for preparing a highly conductive lithium cobalt oxide precursor according to claim 6, wherein: In step S5, the flow rate of the complexing agent solution is 10-150 ml / min, the flow rate of the cobalt salt solution is 10-150 ml / min, the flow rate of the lithium phosphate salt solution is 10-50 ml / min, the flow rate of the precipitant solution is 10-150 ml / min, the flow rate of the molybdenum salt solution is 10-50 ml / min, and the flow rate of the indium salt solution is 10-50 ml / min.

Citation Information

Patent Citations

  • Preparation method of aluminum-doped cobaltosic oxide for 4.5 V lithium cobalt oxide

    CN113213550A

  • Lithium cobalt oxide positive electrode material, preparation method, positive plate and battery thereof

    CN115332498A